Choosing Best Alternative Using Decision Analysis To Maximize Revenue in Company X - Jahja, Ivana; Hermawan, Pri (Jurnal Manajemen Teknologi, 2012)
As a company that moves in retail business specialized in selling daily needs, company X has developed their brand to become top of customers’ mindwith 12% rate of sales growth. However, the Board of Directors (BOD) of company X targeting the rate of sales growth should be 20%, therefore they decide to make an expansion to gain the sales rate, also follow the increasing demand, as well as maintain the customer satisfaction.This research focuses on determining the best alternative that can generate the highest revenue for company X, using decision analysis tools (i.e. smart choice), decision tree and sensitivity analysis. This analysis will be presented in step-by-step in order to be able to generate the best alternatives by understanding the consequences, tradeoff, and uncertainties of the alternative. Keywords:Decision Analysis, Business Expansion, Maximize Revenue, Smart-Choice